The Importance of Urban Corridors in Improving the Green Infrastructure in Cities: Case Study Gaziantep-Turkey - Nasim Shakouri; Mehmet Emin BARIS (Fábos Conference on Landscape and Greenway Planning, 2013)
Rapid urbanization in parallel with population growth is the phenomenon of our century. Urbanization implies great pressure on natural resources and the environment (Rees, 1997; Sandstrom, 2002). Urban growth, by altering cities and the surrounding countryside, presents numerous challenges in urban environment (Tzoulas et al., 2007). As a result of these rapid alterations in urban land use; loss of natural areas, fragmentation of open spaces and degradation of water resources have been occurred over the years. Furthermore, these changes have been influenced the function of ecological services such as provisioning services (e.g. food, fuel, water) to regulating (e.g. climate/air pollution regulation, waste assimilation, flood and fire regulation) that emerged many environmental problems which influenced the quality of human life. Therefore, concerns about the future of cities and next generations’ life in urban area caused the improvement of environmental quality and long-term livability become the main goal of urban planning process. Based on these objectives, the concept of Green Infrastructure gets importance in urban planning and design over the past few decades. Integrating green infrastructure into the land planning process in cities can prevent many environmental problems associated with the human population and protect the natural ecosystem values as well as contribution to the health and quality of life for communities and people. Therefore, the concept of green infrastructure, its benefits and the urban corridors as a tool for improving green infrastructure are focused in this article. Also, Gaziantep city located in Turkey is selected as a case study to clarify these issues.
Keywords: greenways; urban; corridor; green infrastructure; turkey; environment